Capsid-like biodegradable poly-glycolic acid nanoparticles for a long-time release of nucleic acid molecules. Issue 1 (25th November 2020) - Guido, Clara; Testini, Mariangela; D'Amone, Stefania; Cortese, Barbara; Grano, Maria; Gigli, Giuseppe; Palamà, Ilaria E.
Abstract : Capsid-like PGA nanoparticles (NPs) allow sustained cell transfection in 2D and 3D configurations. Abstract : Gene therapy can be described as the direct transfer of genetic material to cells or tissue for the treatment of inherited and acquired diseases. Viral vectors have long been proven to be the most efficient and stable vectors for transgene delivery into the cell, but they still have some safety issues. Non-viral nanosystems can overcome these safety problems and limitations of viral vectors. FDA-approved polymers are particularly attractive for gene delivery applications. Here, sustained release of plasmid DNA encoding the EGFP protein, used as a model, showed efficient delivery through new capsid-like biodegradable polyglycolic acid (PGA) nanoparticles (NPs). PGA NPs showed a mean size of 135 nm, with a polyhedron structure. Prior to loading into the PGA NPs, the pT7-EGFP plasmid was complexed with pH- and enzyme-responsive polycation polymers in order to guarantee high loading, stability, and controlled plasmid release over time. Our PGA NPs are hemocompatible, non-cytotoxic and have the ability to protect the gene cargo from DNase and serum action. Further, our PGA NPs exhibited a controlled and sustained transfection of cells that grow in suspension (human T lymphocytes, Jurkat) and adherent cell lines (human neuroblastoma cells, SH-SY5Y, and human cervix carcinoma cells, HeLa), with respect to transfection with commercial Lipofectamine 3000. In addition, our PGA NPs showed the ability to penetrate into 3D neurospheres, allowing transfection of inner cells. Our capsid-like NPs, thanks to their properties of biocompatibility, biodegradability, hemocompatibility, and sustained plasmid release, can be used as an efficient tool for transfection to overcome the problems of viral vectors.